Association of oxidative balance score with metabolic syndrome and its components in middle-aged and older individuals in the United States - Zhang, Qu; Wu, Yemei; Luo, Bo (Frontiers in Nutrition, 2025)
BackgroundThe prevalence of metabolic syndrome (MetS) among middle-aged and older individuals in the U.S. is rising, posing significant mortality risks. Diet is a key factor in MetS development, yet few studies have examined the combined effects of dietary and lifestyle factors on MetS in this group. Recently, the oxidative balance score (OBS), an indicator of oxidative status encompassing diet and physical activity, has attracted interest. This study explores the association between OBS and MetS, as well as its individual components, in middle-aged and older Americans.MethodsData from 6,157 participants aged 45 years and older in the National Health and Nutrition Examination Survey (NHANES) (1999–2018) were analyzed. The OBS was calculated using 16 dietary and four lifestyle factors. Logistic regression was used to assess associations between OBS and MetS. Separate analyses examined dietary OBS (DOBS) and lifestyle OBS (LOBS) in relation to MetS.ResultsHigher OBS quartiles were associated with a reduced MetS risk (OR 0.25; 95% confidence interval [CI]: 0.12–0.51; p < 0.0001), after adjusting for confounders. Increased OBS was linked to decreases in waist circumference (WC) (OR 0.41; 95% CI: 0.30–0.51; p < 0.0001), triglycerides (TG) (OR 0.71; 95% CI: 0.53–0.92; p = 0.0139), blood pressure (BP) (OR 0.53; 95% CI: 0.40–0.69; p < 0.0001), and fasting glucose (FG) (OR 0.61; 95% CI: 0.45–0.81; p < 0.0001), while HDL-C increased (OR 0.68; 95% CI: 0.51–0.90; p = 0.0065). DOBS was inversely associated with MetS through reductions in BP and FG and increased HDL-C, though it showed no significant effect on WC or TG. LOBS was associated with reductions across WC, BP, FG, TG, and an increase in HDL-C.ConclusionOBS is inversely associated with MetS in middle-aged and older U.S. adults. Enhancing OBS through dietary guidelines emphasizing antioxidant-rich foods, fiber, and unsaturated fats, alongside lifestyle changes like regular exercise, smoking cessation, and moderate alcohol intake, may be crucial in MetS prevention for this population.